Treatment Strategies and Outcome of the Exstrophy–Epispadias Complex in Germany: Data From the German CURE-Net - Ebert, Anne-Karoline; Zwink, Nadine; Reutter, Heiko M.; Jenetzky, Ekkehart; Stein, Raimund; Hölscher, Alice C.; Lacher, Martin; Fortmann, Caroline; Obermayr, Florian; Fisch, Margit; Mortazawi, Kiarasch; Schmiedeke, Eberhard; et al. (Frontiers in Pediatrics, 2020)
Introduction: Introduction: To evaluate the impact of reconstructive strategies and postoperative management on short- and long-term surgical outcome and complications of classical bladder exstrophy (CBE) patients’ comprehensive data of the multicenter German-wide Network for Congenital Uro-Rectal malformations (CURE-Net) were analysed. Patients and Methods: Descriptive analyses were performed between 34 prospectively collected CBE patients born since 2009, median three months old (IQR 2-4), and 113 cross-sectional patients, median 12 years old (IQR 6-21). Results: The majority of included individuals were males (67%). 68% of the prospectively observed and 53% of the cross-sectional patients were reconstructed using a staged approach (p=0.17). Although prospectively observed patients were operated at a younger age, the postoperative management did not significantly change in the years before and after 2009. Solely, in prospectively observed patients peridural catheters were used significantly more often (p=0.017). Blood transfusions were significant more frequent in males (p=0.002). Only half of all CBE individuals underwent inguinal hernia repair. Cross-sectional patients after single-stage reconstructions showed more direct postoperative complications such as upper urinary tract dilatations (p=0.0021) or urinary tract infections (p=0.023), but not more frequent renal function impairment compared to patients after the staged approach (p=0.42). Continence outcomes were not significant different between the concepts (p=0.51). Self-reported continence data showed that the majority of the included CBE patients was intermittent or continuous incontinent. Furthermore, subsequent consecutive augmentations and catheterisable stomata did not significantly differ between the two operative approaches. Urinary diversions were only reported after the staged concept. Conclusions: In this German multicenter study a trend towards the staged concept was observed. While single-stage approaches tended to have initially more complications such as renal dilatation or urinary tract infections, additional surgery such as augmentations and stomata appeared to be similar after staged and single staged reconstructions in the long-term.